PENGARUH RASIO KEUANGAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN CYCLICALS DAN CONSUMER NON CYCLICALS - Edelweis, Vinka Ruth; Kanti, Annisa (E-Jurnal Akuntansi TSM, 2024)
Every company aims to maximize its profits, which benefits expanding business lines, operational efficiency, and enhancing shareholder welfare. One significant factor influencing a reduction in corporate profits is taxation. Consequently, many companies engage in tax avoidance by minimizing the amount of tax payable to the tax authorities. This practice is known as tax aggressiveness. Tax aggressiveness refers to a company's legally permissible actions to minimize its tax obligations through tax management planning. The objective of this research is to analyze empirical evidence regarding Liquidity, Capital Intensity, Sales Growth, Profitability, Inventory Intensity, and Debt to Assets Ratio on Tax Aggressiveness. The study focuses on companies in the cyclical and consumer non-cyclical sectors from the period 2020 to 2022, spanning three consecutive years. Raw data collected was processed using purposive sampling, comprising 67 companies that met the criteria. The data was analyzed using multiple regression models. Results indicate that Liquidity, Inventory Intensity, Debt to Assets Ratio, and Capital Intensity do not influence Tax Aggressiveness, whereas Profitability and Sales Growth do affect Tax Aggressiveness.